2014
DOI: 10.4068/cmj.2014.50.3.86
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propofol on microRNA Expression Profile in Adipocyte-Derived Adult Stem Cells

Abstract: MicroRNA (miRNA) pathways have been implicated in stem cell regulation. This study investigated the molecular effects of propofol on adipocyte stem cells (ASCs) by analyzing RNA expression arrays. Human ASCs were isolated by use of a liposuction procedure. ASCs were treated with saline, 50 µM propofol, or 100 µM propofol in culture media for 3 hours. After the isolation of total RNA, the expression of 76 miRNAs was evaluated with peptide nucleic acid-miRNA array analysis through denaturation and hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[131][132][133] other studies demonstrated effects of propofol on human stem cells, leading to alterations in mirNA expression levels. 15,134 in addition, some recent studies also indicate functional relevance for certain mirNAs in the pathogenesis or protection from neurotoxicity, respectively. Moreover, some mirNAs have already been identified to present potential targets that could be modulated to enhance the mirNA-mediated neuroprotective effects.…”
Section: Role Of Mirnas In Mediating Anesthetic Toxicitymentioning
confidence: 99%
“…[131][132][133] other studies demonstrated effects of propofol on human stem cells, leading to alterations in mirNA expression levels. 15,134 in addition, some recent studies also indicate functional relevance for certain mirNAs in the pathogenesis or protection from neurotoxicity, respectively. Moreover, some mirNAs have already been identified to present potential targets that could be modulated to enhance the mirNA-mediated neuroprotective effects.…”
Section: Role Of Mirnas In Mediating Anesthetic Toxicitymentioning
confidence: 99%
“…This process forms a continuous lesion, which frequently occurs over 10 years (14). Early identification and timely treatment can substantially improve the survival rate of patients with cervical squamous carcinoma (15). Therefore, investigating the mechanisms underlying the invasion and metastasis of cervical cancer cell is of the highest priority (16).…”
Section: Discussionmentioning
confidence: 99%
“…131133 Other studies demonstrated effects of propofol on human stem cells, leading to alterations in miRNA expression levels. 15,134 In addition, some recent studies also indicate functional relevance for certain miRNAs in the pathogenesis or protection from neurotoxicity, respectively. Moreover, some miRNAs have already been identified to present potential targets that could be modulated to enhance the miRNA-mediated neuroprotective effects.…”
Section: Pharmacologic Functions Of Mirnas and Mirna Therapeuticsmentioning
confidence: 99%